Business Intelligence 5th European Summer School, eBISS 2015, Barcelona, Spain, July 5-10, 2015, Tutorial Lectures - Zimányi, Esteban; Abelló, Alberto (Lecture Notes in Business Information Processing, 2016)
This book constitutes the tutorial lectures of the 5th European Business Intelligence Summer School, eBISS 2015, held in Barcelona, Spain, in July 2015. The tutorials presented here in an extended and refined format were given by renowned experts and cover topics including schema evolution for databases and data warehouses, publishing OLAP cubes on the Semantic Web, design issues in social business intelligence projects, context-aware business intelligence, and key performance indicators in data warehouses.